If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -1(8k + 4) = -2k + 6 Reorder the terms: 2k + -1(4 + 8k) = -2k + 6 2k + (4 * -1 + 8k * -1) = -2k + 6 2k + (-4 + -8k) = -2k + 6 Reorder the terms: -4 + 2k + -8k = -2k + 6 Combine like terms: 2k + -8k = -6k -4 + -6k = -2k + 6 Reorder the terms: -4 + -6k = 6 + -2k Solving -4 + -6k = 6 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. -4 + -6k + 2k = 6 + -2k + 2k Combine like terms: -6k + 2k = -4k -4 + -4k = 6 + -2k + 2k Combine like terms: -2k + 2k = 0 -4 + -4k = 6 + 0 -4 + -4k = 6 Add '4' to each side of the equation. -4 + 4 + -4k = 6 + 4 Combine like terms: -4 + 4 = 0 0 + -4k = 6 + 4 -4k = 6 + 4 Combine like terms: 6 + 4 = 10 -4k = 10 Divide each side by '-4'. k = -2.5 Simplifying k = -2.5
| t^2-4t=21 | | 0.75(4x+12)=-20 | | v-4.025=-1.9024 | | -90=18-12v | | -8d-29=-77 | | 16+3d=d | | 25-9p=-11 | | y-16=23 | | y(3n^3-3n^2+n+1)=0 | | 8=-4k^2 | | p^3+9p^2+4p+36=0 | | ln(2x+5)+ln(x-5)-2ln(x)=0 | | 3x+5(x-1)=27 | | 0.3(3w-6)=-0.5(2w-4) | | 3x+3=15whatsx | | 8p-12p=0 | | x^3+2x^2+5x-4=0 | | x^3-2x^2+5x-4=0 | | 12+8= | | x^3-x^2+5x-4=0 | | 0.5(t-1)=0.25(t-3) | | 10-2x=6x+22 | | 8x+1=4x | | 0.5(x-1)=0.5(-4x+8) | | 5x-.5=.5 | | 50x^2+15x-5=0 | | 5n-4(n-8)=3+2n | | y^2+6y+7=0 | | 30x^2-156x-144=0 | | 8(y-1)=4y+20 | | a^2+14a+49-64n^2= | | 8x+5=26+35 |